Relative Frequency and Risk Factors for Prolonged Opioid Therapy after Surgery and Trauma: A Systematic Review and Meta-Analysis - M Gabrielle Pagé; Irina Kudrina; Patrice Ngangue; Maude Fortier; Elisabeth Martin; Esthelle Ewusi-Boisvert; Hervé T V Zomahoun; Jordie Croteau; Daniela Ziegler; Pierre Beaulieu; Céline Charbonneau; Jennifer Cogan; et al. (Taylor & Francis Group, 2019)
Introduction/Aim: The objectives of this systematic review and meta-analysis were to examine the relative frequency and risk factors (patient, surgical, medical, clinical) for prolonged opioid therapy among surgical and trauma patients. Methods: Studies published in English and French between 1998 and April 2018 examining risk factors for prolonged (3-6 months) or chronic (>6 months) opioid use after surgery/trauma were included. Literature search: seven databases were queried, empirical studies were identified via direct and back citation search, grey literature was also included. A minimum of two independent reviewers assessed studies for inclusion, extracted data and assessed studies quality. Results: Thirty-five out of 10,003 screened articles were included. The median relative frequency of prolonged (50.9%) and chronic (58.5%) opioid therapy among pre-event patients already on opioid therapy was much higher compared to pre-event opioid naïve patients (4.1% and 2.6%, respectively). Tobacco use, depressive disorder and antidepressants use were significant risk factors for prolonged and/or chronic opioid therapy among pre-event opioid naïve patients. Tobacco use, depressive disorder and history of migraines were risk factors for prolonged opioid therapy among pre-event opioid-treated patients. Discussion/Conclusions: Prevention initiatives to reduce the risk of prolonged opioid therapy after surgery or trauma should target specific health behaviors and psychiatric disorders; these interventions should be tailored based on patients' pre-event opioid status.